Growing in Revere: Recommendations for Community Food System Development. - Auch, Casey.; Fulgione, Brittany.; Kubota, Abigail.; Peña, Yaritza. (Tufts University. Tisch Library., 2023)
2022 M.A./M.S. in Urban and Environmental Policy and Planning Field Project. Client: Revere on the Move, City of Revere Department of Community Health, Revere CARES Coalition.